2014
DOI: 10.1186/1475-925x-13-53
|View full text |Cite
|
Sign up to set email alerts
|

A compact theory of magnetic nerve stimulation: predicting how to aim

Abstract: BackgroundA compact theory that predicts quantitatively when and where magnetic neurostimulation will occur is needed as a guide to therapy, ideally providing a single equation that defines the target volume of tissue excited by single or dual coils.MethodsA first-principles analysis of magnetic stimulation incorporating a simplified description of electromagnetic fields and a simplified cable theory of the axon yields a mathematical synthesis predicting how to aim.ResultsNerve stimulation produced by a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
1
2
0
2
Order By: Relevance
“…In Type II stimulation, if the stimulation pulse is sufficiently wide, then both the rising and the falling phases of the induced electric field can depolarize the membrane (at different locations) and initiate action potentials. This modeling result is in agreement with a previous study (Babbs, 2014), which reported that axon segments in a sub-millimeter scale were the sites of magnetic stimulation. The axonal membrane at one end was depolarized locally during the rising phase of current in the coil.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In Type II stimulation, if the stimulation pulse is sufficiently wide, then both the rising and the falling phases of the induced electric field can depolarize the membrane (at different locations) and initiate action potentials. This modeling result is in agreement with a previous study (Babbs, 2014), which reported that axon segments in a sub-millimeter scale were the sites of magnetic stimulation. The axonal membrane at one end was depolarized locally during the rising phase of current in the coil.…”
Section: Discussionsupporting
confidence: 93%
“…The axonal membrane at one end was depolarized locally during the rising phase of current in the coil. The axonal membrane at the opposite end was depolarized locally during the falling phase of current in the coil (Babbs, 2014 ). Similarly, Maccabee et al ( 1993 ) also reported that a polyphasic pulse excited the nerve at two different sites on the axon by a negative first phase at one location and by a reversed second phase at the other location.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic fields have been shown to easily pass skin, skull and brain tissue (Murphy and Persinger, 2011, Nummenmaa et al, 2013, Bonmassar et al 2012, Babbs, 2014 and this have been related to a toroidal computing process of neural oscillations and Ca2+ pulsing, in which all collaborative effort of glia cells also plays a role (see also Pereira and Furlan, 2007;Pereira, 2017). These aspects highlight the rising interest for electromagnetic correlates in consciousness studies (Liboff, 2017;Prakash et al 2008), in which, among other mechanisms magnetic activation of slow acting voltage-gated Ca2+ channels could play a prominent role (Bonmassar et al, 2012).…”
Section: -Quantum Coherence Mediated Brain Functionmentioning
confidence: 99%
“…Одной из перспективных физиотерапевтических методик является ритмическая периферическая магнитная стимуляция (рПМС) [9,10]. Физиологические основы метода рПМС связаны с воздействием наведенного электрического тока, т. е. возникающего в результате электромагнитной индукции, с последующей активацией проводниковых структур периферической и центральной нервной системы [11,12].…”
Section: Introductionunclassified